2011
DOI: 10.1080/17461391.2010.499972
|View full text |Cite
|
Sign up to set email alerts
|

Influence of opposition team formation on physical and skill‐related performance in a professional soccer team

Abstract: This study examined the influence of opposition team formation on physical and skillrelated performance in a professional soccer team. Performance in forty-five French League 1 matches played over three competitive seasons (2007-08, 2008-09, and 2009-10) was analysed using multi-camera computerised tracking. Players (n=21) in the reference team (using a 4-3-3/4-5-1 formation) were analysed in matches against three opposition team formations: 4-4-2 (11 games), 4-3-3/4-5-1 (16 games) and 4-2-3-1 (18 games). Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 20 publications
3
57
0
5
Order By: Relevance
“…Changes over the consecutive games in the reference team's choice of starting line-up and tactics and/or in the specific physical and skill demands, playing style and team formation imposed by 8 separate opponents [4,16,25] could explain these variations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes over the consecutive games in the reference team's choice of starting line-up and tactics and/or in the specific physical and skill demands, playing style and team formation imposed by 8 separate opponents [4,16,25] could explain these variations.…”
Section: Discussionmentioning
confidence: 99%
“…4 It has recently been suggested that professional soccer players regulate their physical efforts when participating in congested fixture periods [27]. While this selfimposition of efforts might partly explain the previously observed lack of a decline in physical performance during successive games with a short recovery period, no studies have verified this theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actualmente, los investigadores utilizan esta tecnología, fundamentalmente para conocer el rendimiento físico (Castellano, Blanco-Villaseñor, y Álvarez, 2011;Di Salvo y col, 2007) o físico-técnico de los jugadores (Carling, 2011;Dellal, Wong, Moalla, y Chamari, 2010), aunque su aplicación en la identificación de indicadores tácticos de rendimiento (Lames y McGarry, 2007) es una realidad inminente (Sampaio y Maçãs, 2012). Con la implementación de esta tecnología al deporte, comienza a resultar no muy complicado disponer de las variables espacio-temporales que pueden ser relevantes para comprender la complejidad táctica del juego.…”
Section: Introductionunclassified
“…From football evidence has also been provided by Egil Olsen (1997) on how PA impacted directly on the Norwegian national team's playing style (Olsen & Larsen, 1997, Pollard 2002, Weaver, 2007. More recently, much of the match analysis research conducted by Carling's research group has attempted to address key performance questions within the club in which the researcher works and as a result has had a direct impact on the club's approaches and practices Carling & Dupont, 2011;Carling & Bloomfield, 2010;Carling, 2011). However little is still known as to what information derived from PA coaches do and do not value, how the information collected is used to affect their decision making and subsequent planning of training, tactical strategies and approaches.…”
Section: How Is Performance Analysis Commonly Used: Quantitative Apprmentioning
confidence: 99%